TUBERCULOSIS MENINGITIS IN CHILDREN: MODERN REQUIREMENTS TO DIAGNOSTICS - L. V. Klochkova; M. E. Lozovskaja; E. B. Vasilyeva; Yu. A. Yarovaja (Журнал инфектологии, 2018)
Тhe aim: to analyze reasons of late diagnostics and course specifics of tuberculosis meningitis (TBM) in children in Saint Petersburg, Russia.Materials and methods: Data was obtained from the Russian official statistics on the frequency of childhood tuberculosis meningitis in 2000-2016. We also analyzed the frequency, the course and the diagnostic specifics of tuberculosis meningitis in children in 2005–2016 in Saint Petersburg.Results and discussion: In the Russian Federation the number of children diagnosed with tuberculosis meningitis per year was reduced from 51 in 2000 to 13 in 2016. In Saint Petersburg over the period of 2005 to 2016 there were seven registered cases of childhood tuberculosis meningitis. Unfortunately only three children out of seven in Saint Petersburg tuberculosis meningitis cases survived. The main factors associated with tuberculosis meningitis in children were young age, children three years old and younger (5 out of 7 children), the presence of a TB patient in the family (6 out of 7 children), lack of BCG vaccination (5 out of 7 children), and poor socio-economic situation (5 out of 7 children). Three out of seven children developed tuberculosis meningitis after becoming HIV positive. The following methods of tuberculosis meningitis diagnostics exist in Russia: Diaskintest, PCR, and Bactec culture tests for Mycobacterium tuberculosis. QuantiFERON-TB Gold and T-SPOT.TB are available but too expensive for most patients. However, a low prevalence of tuberculosis meningitis cases resulted in insufficient attention to TBM, late diagnostics and fatal cases. Three clinical cases were analyzed.Conclusion: To improve tuberculosis meningitis treatment outcomes it is necessary to raise awareness of TB infection among treatment providers, especially when evaluating high risk children population. It is critical to determine presence of latent Mycobacterium tuberculosis, use all etiological diagnostic methods, including PCR and Bactec, when analyzing cerebrospinal fluid and other specimen, and initiate anti-TB treatment immediately when tuberculosis meningitis is suspected.